Breakthrough of SIV strain smE660 challenge in SIV strain mac239-vaccinated rhesus macaques despite potent autologous neutralizing antibody responses - Burton, Samantha L. (Proc Natl Acad Sci U S A, 2015)
Although the correlates of immunological protection from human immunodeficiency virus or simian immunodeficiency virus infection remain incompletely understood, it is generally believed that medium to high titers of serum neutralizing antibodies (nAbs) against the challenge virus will prevent infection. This paradigm is based on a series of studies in which passive transfer of HIV-specific nAbs protected rhesus macaques (RMs) from subsequent mucosal challenge with a chimeric human/simian immunodeficiency virus. However, it is unknown whether nAb titers define protection in the setting of active immunization. Here we determined serum nAb titers against breakthrough transmitted/founder (T/F) SIVsmE660-derived envelope glycoprotein (Env) variants from 14 RMs immunized with SIVmac239-based DNA-prime/modified vaccinia virus Ankara-boost vaccine regimens that included GM-CSF or CD40L adjuvants and conferred significant but incomplete protection against repeated low-dose intrarectal challenge. A single Env variant established infection in all RMs except one, with no identifiable genetic signature associated with vaccination breakthrough compared with T/F Envs from four unvaccinated monkeys. Breakthrough T/F Env pseudoviruses were potently neutralized in vitro by heterologous pooled serum from chronically SIVsmE660-infected monkeys at IC(50) titers exceeding 1:1,000,000. Remarkably, the T/F Env pseudoviruses from 13 of 14 monkeys were also susceptible to neutralization by autologous prechallenge serum at in vitro IC(50) titers ranging from 1:742–1:10,832. These titers were similar to those observed in vaccinated RMs that remained uninfected. These data suggest that the relationship between serum nAb titers and protection from mucosal SIV challenge in the setting of active immunization is more complex than previously recognized, warranting further studies into the balance between immune activation, target cell availability, and protective antibody responses.